2021
DOI: 10.20916/1812-3228-2021-1-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Eye-Movement Techniques in Indirect Nominal Groups Entrenchment

Abstract: The study reveals the reading and construal techniques employed in the process of textual entrenchment of indirect nominal groups. Entrenchment is characterized by the conventionalization of the nominal group form and the repeated referent construal scheme. The research discloses whether any repeated indirect nominal group use contributes to its entrenchment which is assessed in the oculographic experiment. It traces the eye-movement techniques and the reference identification index variations signifying the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results demonstrate that creative language use in its novel and entrenched variants still has several common effects onto its gaze perception which appear to be steady with the participants with worse memory. Therefore, the findings extend the eye-tracking experimental results obtained in (Cardillo et al, 2012;Goldstein et al, 2012;Kiose & Kharlamova, 2021) which state the differences only for novel and entrenched metaphors gaze costs. Even though the novel indirect name is used repeatedly, the participants face multiple challenges in the event construal in AoIs which affect their reading strategy.…”
Section: Theoretical and Applied Linguisticssupporting
confidence: 88%
See 2 more Smart Citations
“…The results demonstrate that creative language use in its novel and entrenched variants still has several common effects onto its gaze perception which appear to be steady with the participants with worse memory. Therefore, the findings extend the eye-tracking experimental results obtained in (Cardillo et al, 2012;Goldstein et al, 2012;Kiose & Kharlamova, 2021) which state the differences only for novel and entrenched metaphors gaze costs. Even though the novel indirect name is used repeatedly, the participants face multiple challenges in the event construal in AoIs which affect their reading strategy.…”
Section: Theoretical and Applied Linguisticssupporting
confidence: 88%
“…This can be explained if we consider that in context novel metaphors may become entrenched through their repeated use and consequently lower gaze costs will be observed (Cardillo et al, 2012;Goldstein et al, 2012). In the previous study (Kiose & Kharlamova, 2021) we reported the results on the construal differences observed in novel and entrenched metaphors separately, however these results allowed to predict that there might be significant construal and gaze cost contingencies irrespective of metaphor novelty / entrenchment but dependent on other metaphor construal factors like agentivity or degree of abstractness.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation